Immunologic aspects of atopic dermatitis - Lipozenčić, Jasna (Array, 2009)
Summary: Atopic dermatitis/eczema is a chronically relapsing, pruritic, and inflammatory skin disease. The term “atopic eczema/ dermatitis syndrome” covers the “extrinsic” and “intrinsic” atopic dermatitis. The pathogenesis of atopic dermatitis includes complex interaction between the genetic background, skin barrier defects, abnormalities in innate and adaptive immunity, abnormalities of humoral and cellular immunity, and environmental influences. Understanding the immunopathogenesis of atopic dermatitis leads to new diagnostic and therapeutic approaches. The targets in atopic dermatitis are innate immunity including improvement of skin barrier defects by supplementing lipids or inhibiting proteases, and regulating antimicrobial peptides, adaptive immunity, and induction of regulatory T cells